Inequality configurations - Letícia Barbabela; Miquel Pellicer; Eva Wegner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The notion of multidimensional inequality has attracted attention lately, but mostly as a micro approach to measuring inequality in well-being in a more complete way. We argue that considering inequality in a multidimensional way from a macro perspective is useful for a better understanding of the structure of inequality in different societies. Different societies display different degrees of inequality in different domains, such as the economic, social, political, and psychological. In this paper, we ask how these inequalities relate to each other and what inequality configurations societies display as a result. Are different inequalities simply a manifestation of one single basic dimension of inequality so that some countries are egalitarian in everything while other countries are fundamentally inegalitarian? Or are inequalities in different domains largely unrelated? We compile a dataset of 98 countries, merging income inequality data from the World Income Inequality Database, health (length-of-life) inequality data from life tables, and inequality measures of political participation, perceived political influence, self-efficacy, and social class compiled from a large set of cross-country attitudes surveys. Our results suggest two distinct dimensions of inequality. The first and by far more important captures socioeconomic and psychological inequality and we find that inequalities in income, health, social class, and selfefficacy are strongly related. A second, less important but still relevant, dimension of inequality concerns political inequality. These two underlying dimensions of inequality correlate differently with relevant outcomes. The socioeconomic/health/psychological inequality component correlates with life satisfaction, satisfaction with democracy, and violent protest. The political inequality component correlates with satisfaction with democracy and peaceful protest.
Keywords: D63; I14; D72; P50; 330; multidimensional inequality; WIID; inequality regimes